Serum Vitamin D in patients with alopecia areata - Ola Ahmed Bakry; Shawky M El Farargy; Maathir K El Shafiee; Amira Soliman (Wolters Kluwer Medknow Publications, 2016)
Background: Alopecia areata (AA) is a common, recurrent, autoimmune hair disorder. It has been found that vitamin D deficiency is associated with many autoimmune diseases. Aims: The current study aimed to estimate serum levels of 25-hydroxy vitamin D in patients with AA. Materials and Methods: This case-control study included 60 patients with AA and 60 age, gender, skin phototype, and body mass index-matched healthy subjects as a control group. Levels of serum 25-hydroxy vitamin D were estimated using ELISA technique. Results: Serum 25-hydroxy vitamin D levels were significantly lower in AA cases when compared with healthy controls (P < 0.001). The least values were significantly associated with alopecia totalis/universalis compared with patchy AA (P< 0.001) and ophiasis (P = 0.04). Severe AA showed significantly the lowest vitamin D levels compared with cases with mild (P = 0.002) and moderate disease (P = 0.03). A significant inverse correlation was found between 25-hydroxy vitamin D levels and age of the patients (r = −0.38; P = 0.03). There was no significant association between serum 25-hydroxy vitamin D levels and gender, disease duration, disease recurrence, nail affection, duration of sun exposure/day, or positive family history of AA. Conclusion: AA patients have lower levels of 25-hydroxy vitamin D than healthy subjects. More studies are required to assess the value of vitamin D supplementation in the treatment of that disease.